The molecular basis of the Fragile X syndrome - Harem Othman smail (Journal of Experimental and Molecular Biology, 2023)
This analysis aimed to clarify the molecular basis of fragile X syndrome and explain the role of genetic material in the genetic disease's development and treatment. Fragile X syndrome is an X-linked mutation inheritance disorder. The mutated gene is called FMR-1. This is important for normal brain development and synaptic plasticity, which was verified and recognized in 1991, and this has become a hope for more clarification. FMR1 influences the translation of messenger RNA (mRNA), but identifying functional targets was complex and directly related to translational control and showed that dysregulated translation initiation signaling was observed for the FMR1 gene in the FMR1 knockout mouse model of FXS.